Deer Exclusion Changes Vegetation Structure and Hunting Guilds of Spiders, but Not Multitrophic Understory Biodiversity - Roman Bucher; Jonas Rochlitz; Nathalie Wegner; Anna Heiß; Alexander Grebe; Dana G. Schabo; Nina Farwig (Diversity, 2021)
Ungulate herbivores modify plant community compositions, which can modulate biodiversity at higher trophic levels. However, these cascading effects on herbivorous and predatory arthropods in forest ecosystems remain poorly understood. We compared plant and arthropod communities between fenced exclosures and unfenced control plots in a permanent forest in Germany. After five years of deer exclusion, we quantified plant diversity and vegetation structure as well as the diversity of insects and spiders in 32 pair-wise plots. In addition, we compared spider communities with respect to different hunting guilds because they are expected to have different requirements for vegetation structure. Although we did not find differences in plant communities, vegetation height and heterogeneity were higher in exclosures compared to control plots. The diversity of insects and spiders was not affected by deer presence. However, the abundance of sheet-web weavers and ambush hunters was lower in exclosures whereas ground hunters were more common in exclosure plots. Structural changes in the vegetation changed predator hunting guilds even though mere abundance and biodiversity indices were not affected. We therefore suggest that monitoring of vegetation structure and associated functional groups seems more sensitive to assess the impact of ungulate herbivores compared to taxonomic metrics.